A Review on the Perspective of Peptic, Mouth and Corneal Ulcer and Their Treatment Facts - Kumar, Banik Rony; J, Mallik (Asian Journal of Pharmaceutical Research and Development, 2018)
The stomach is a bag of muscle that crushes and mixes food with the digestive "juices" - hydrochloric acid and pepsin. An ulcer is the result of an imbalance between aggressive and defensive factors. On one hand, too much acid and pepsin can damage the stomach lining and cause ulcers. The primary cause of ulcers is the bacterium called Helicobacter pylori (H. pylori). H. pylorus is a spiral-shaped bacterium found in the stomach. Although H. pylori is the primary cause of ulcers, there are other factors that play a role in ulcer development. NSAIDs such as aspirin, ibuprofen, naproxen, interfere with the stomach's ability to produce mucus and bicarbonate (a chemical produced in the stomach that neutralizes and breaks down the hydrochloric acid and pepsin into substances less harmful). Peptic ulcers are generally caused by an acid resistant bacterium called Helicobacter pylori (H. pylori) which infect the stomach. H pylorus is Gram negative spiral shaped bacteria. In human it colonizes in stomach and the likelihood of infections increases with age. The sensitivity and specificity of Biopsy urease test which detect H. pylori urease enzyme activity are above 90%. Urea breath test is based on urease production by H. pylori. The carbon 13 (Non radio active isotope) and carbon 14 (Radio active isotope) tests require that the patient ingest labeled urea, which is broken down in the stomach to ammonia and labeled bicarbonate